Experimental Investigation of the Influence of Climatic Conditions and Vehicle Dynamics on the Thermal Management System of a Fuel Cell Electric Vehicle - Yannick Heynen; Ralf Liedtke; Michael Schier; Florian Heckert (Energies)
In this study, the cooling performance of fuel cell electric vehicles (FCEVs) with regard to thermal derating is investigated. Particularly in hot climate conditions, low operating temperature of the fuel cell stack and hence low temperature difference to the environment can result in thermal derating of the fuel cell stack. Experimental investigations on a production vehicle with a fuel cell drive (Hyundai Nexo) are conducted to analyze the influence of climatic boundary conditions and a dynamic driving scenario on the thermal management system of the vehicle. Therefore, a new method based on energy balances is introduced to indirectly measure the average cooling air velocity at the cooling module. The results indicate that the two high-power radiator fans effectively maintain a high cooling airflow between a vehicle speed of approximately 30 and 100 <semantics>km/h</semantics>, leading to efficient heat rejection at the cooling module largely independent of vehicle speed. Furthermore, this study reveals that the efficiency of the fuel cell system is notably affected by ambient air temperature, attributed to the load on the electric air compressor (EAC) as well as on cooling system components like cooling pump and radiator fans. However, at the stack level, balance of plant (BoP) components demonstrate the ability to ensure ambient temperature-independent performance, likely due to reliable humidification control up to 45 °C. Additionally, a new method for determining thermal derating of FCEVs on roller dynamometer tests is presented. A real-world uphill drive under ambient temperatures exceeding 40 °C demonstrates derating occurring in 6.3% of the time, although a worst case with an aged stack and high payload is not investigated in this study. Finally, a time constant of 50 <semantics>s</semantics> is found to be suitable to correlate the average fuel cell stack power with a coolant temperature at the stack inlet, which gives information on the thermal inertia of the system observed and can be used for future simulation studies.